Strategi Manajemen Bayt Al - Qur’an Al - Akbar Kota Palembang Dalam Meningkatkan Daya Tarik Wisata Religi - Rahmat Febrian; Kusnadi Kusnadi; Anang Walian (Social Science and Contemporary Issues Journal, 2024)
This research aims to find out what management strategies are related to the management mix implemented by the Bayt Al-Quran Al-Akbar Palembang religious tourist attraction. Using descriptive-qualitative methods with data collection techniques through interviews, observation and documentation which aims to provide an overview or describe the existing reality or what happened to the object under study. The results of this research show that the management strategy used in Bayt Al-Quran Al-Akbar has a big impact on increasing the attractiveness of religious tourism, and Bayt Al-Quran Al-Akbar shows that religious tourism Al-Quran Al-Akbar has extraordinary potential as a Palembang City religious tourist attraction.